2017
DOI: 10.1177/0960327117702952
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic exposure to palladium nanoparticles affects serum levels of cytokines in female Wistar rats

Abstract: Recently, palladium nanoparticles (PdNPs) have been increasingly used in many industrial sectors, and this has led to a significant release of nano-sized palladium particles into the environment. However, despite the increase in occupational and general population exposure, information on the potential adverse effects of these PdNPs is still limited and their impact on the immune system constitutes a major health concern. Therefore, the aim of this study was to investigate the potential adverse effects induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
2
16
1
Order By: Relevance
“…Other studies have mentioned the interaction between nanoparticles and circulating immune cells or secondary lymphoid tissues. In present work, DNA quantification and cell cycle analysis in bone marrow indicated non-significant changes [41,42]. Our results agree with previous reports regarding the presence of an initial state of inflammation; afterwards, however, an anti-inflammatory state predominantes.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have mentioned the interaction between nanoparticles and circulating immune cells or secondary lymphoid tissues. In present work, DNA quantification and cell cycle analysis in bone marrow indicated non-significant changes [41,42]. Our results agree with previous reports regarding the presence of an initial state of inflammation; afterwards, however, an anti-inflammatory state predominantes.…”
Section: Discussionsupporting
confidence: 92%
“…The subchronic exposure to increased doses of PdNPs induced a decreasing trend in serum levels in most of the cytokines investigated [102]. The finding showed that PdNPs strongly affected the immune system of treated rats [102]. Chen et al [65] reported the size-dependent toxicity of Pd nanosheets.…”
Section: Toxicitymentioning
confidence: 99%
“…Concerning in vivo results, the target effect of PdNPs is on the immune, renal, and endocrine systems [101]. Iavicoli et al studied the potential immunotoxic impact of immunostimulatory and immunosuppressive effects of PdNPs on Wistar rats [102]. The subchronic exposure to increased doses of PdNPs induced a decreasing trend in serum levels in most of the cytokines investigated [102].…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several biological models, from bacterial strains [ 51 ] to mammalian organisms were reported to be affected by Pd-NP treatment. The immune [ 52 , 53 ], renal [ 54 ] and endocrine systems [ 55 ] were demonstrated as critical targets for the toxic action of Pd-NPs ( Table 2 ). The elemental Pd content in urine, and changes in cytokine serum levels, urinary protein content and hormonal serum concentrations, emerged as possible biomarkers of Pd-NP exposure and early effect, although further studies are necessary to confirm these preliminary results and validate their possible employment in real exposure settings.…”
Section: In Vivo Studiesmentioning
confidence: 99%